REVISITING PHOTOGRAPHIC MEMORY IN CLASH OF CHAMPIONS: HOW TO INTEGRATE PHOTOGRAPHIC MEMORY IN ENGLISH LANGUAGE TEACHING (ELT)? - Nur Fitria, Tira (International Journal of English Learning and Applied Linguistics (IJELAL), 2024)
This research explores the integration of photographic memory principles into English Language Teaching (ELT), focusing on descriptive qualitative methods. Photographic memory (eidetic memory), enables individuals to vividly remember visual stimuli after brief exposure, which is crucial in contexts like ELT where retention and recall are paramount. Integrating these principles into ELT emphasizes active learning and memory retention to enhance language proficiency through engaging tasks that mirror real-world language use. Educators utilize visual, mnemonic, contextual, and interactive strategies alongside repetition, review, and multi-sensory approaches to optimize learning outcomes. This approach not only supports students in mastering English skills but also fosters cognitive abilities related to memory and learning. In ELT, photographic memory proves invaluable across various domains. Students with this ability excel in vocabulary acquisition by associating words with mental images or visual cues, aiding retention. They also benefit from vividly recalling grammar rules and sentence structures presented in class, enhancing comprehension. Moreover, photographic memory assists in reading comprehension by facilitating accurate recall of text details, thereby improving students' ability to analyze and discuss content effectively. In developing pronunciation and listening skills, these learners leverage memory to replicate correct models and remember spoken phrases accurately, crucial for language acquisition. Lastly, in exams like TOEFL or IELTS, where memorization is crucial, students with photographic memory excel in quickly retrieving and applying knowledge, significantly enhancing their exam performance. Integrating photographic memory principles into ELT not only enhances language learning outcomes but also nurtures overall engagement and cognitive development, making it a powerful tool in educational contexts focused on language proficiency and academic achievement.